Analisis dampak belanja modal dan tingkat pengangguran terhadap tingkat kemiskinan di Kabupaten Tebo - Yoga Amanda; Zamzami Zamzami; Selamet Rahmadi (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
This study aims to determine and analyze: 1). Changes that occur in capital expenditure, unemployment, and the number of poor people in Tebo Regency during 2004-2018, 2). Effect of capital expenditure and unemployment rates on poverty levels in Tebo Regency during 2004-2018. The data analysis method used in this study uses the formula of development and multiple linear regression. Based on the results of research during 2004- 2018 in Tebo Regency, the average capital expenditure increases 20.99 percent every year, the number of unemployed people has increased 28.57 percent every year and the average number of poor people has decreased 0, 42 percent every year. Capital expenditure and unemployment rate influence reducing the level of poverty in Tebo Regency during 2004-2018 with a regression coefficient value of capital expenditure and the unemployment rate which has a negative regression coefficient. Keywords: Capital expenditure, Poverty rate, Unemployment rate